2019
DOI: 10.1111/jfpp.14327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different preparation methods on the development of chitosan/thyme oil/montmorillonite nanocomposite active packaging films

Abstract: The globally increasing needs for food quantity and quality led industries to invest in packaging methods that enhance the shelf life and quality of foods. Also, the effort to avoid the use of petrochemical or chemical derivatives in the production‐chain increased the exploitation of by‐products and biomass. In this work, the raw materials such as montmorillonite (Mt), the chitosan (CS) which is a sea‐food byproduct, and the natural essential oil extract thyme oil (TO) were combined via two different methods f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 74 publications
(137 reference statements)
2
24
0
Order By: Relevance
“…Giannakas et al [24] used a "ModifiedClay (MC)" method to adsorb thymol EO into MMT to obtain hybrid EO systems for the preparation of nanocomposite films with improved tensile strength, water swelling and barrier properties to be used as active food packaging materials. Similar results were found by other authors when different EOs were incorporated into MMT [41][42][43].…”
Section: Hybrid Systems With 100 Wt% Leomentioning
confidence: 99%
See 1 more Smart Citation
“…Giannakas et al [24] used a "ModifiedClay (MC)" method to adsorb thymol EO into MMT to obtain hybrid EO systems for the preparation of nanocomposite films with improved tensile strength, water swelling and barrier properties to be used as active food packaging materials. Similar results were found by other authors when different EOs were incorporated into MMT [41][42][43].…”
Section: Hybrid Systems With 100 Wt% Leomentioning
confidence: 99%
“…The high volatility of EOs is their main drawback in several applications that require temperature processing, such as in the case of polymer nanocomposites, leading to EO losses by evaporation during polymer processing [23]. The encapsulation of EOs into nanoclays has been proved to be suitable for protecting and preserving the effectiveness of the EO bioactive substances in storage, providing a controlled release of EOs into the polymer matrix [24]. The preparation of MMT-essential oil powders with oregano, thyme and basil oils was reported showing a significant modification in the basal space of MMT clay and increased EO thermal stability with the EO adsorption [17,25].…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that adsorption of EO onto an inorganic porous material [ 8 , 9 ] could provide controlled release and protection against polymer processing conditions. In this direction, EO nanocarriers, such as commercial organically modified montmorillonite (OrgMt) [ 10 ] and halloysite [ 11 , 12 ], used in polymers-based [ 6 , 13 , 14 , 15 ] and biopolymers-based [ 16 , 17 , 18 , 19 ] active packaging films. Shemesh et al [ 11 ] adsorbed carvacrol into halloysite nanotubes and developed low-density poly-ethylene (LDPE)/carvacrol/halloysite antimicrobial films.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the strong polar chemical bonds chitosan–chitosan will be replaced by weaker interactions between chitosan–GEO. Giannakas et al (2020) [ 76 ] observed similar results when introduced thyme oil in two different chitosan/MMT structures. As expected, they noted that the introduction of nanoclays, MMTNa + and OrgMMT, improved mechanical behavior.…”
Section: Nanotechnology As Reinforcementmentioning
confidence: 69%